Recovery Strategy Sistem Pendidikan dalam Membangun Kepercayaan Pelanggan pada Perguruan Tinggi Swasta di Universitas Nusantara PGRI (UNP) Kediri - Khafidhotun Nasikhah; Prim Masrokan Mutohar; Agus Eko Sujianto (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
This important study aims to explore in greater depth the system recovery strategy implemented by UNP Kediri to restore the institution’s health following the crisis it experienced in 2015—namely, the suspension of campus operations—and how UNP Kediri has since been able to rebound, grow, and become competitive, ultimately regaining the trust of its stakeholders through a strategic recovery plan for the university. The recovery strategy was implemented comprehensively by examining the university’s challenges, which highlighted the need for a simple strategic revitalization model. This study employed a qualitative research method using a case study approach. Data collection techniques included in-depth interviews, document analysis, and observation. To ensure data validity, the researcher assessed credibility, dependability, and confirmability. Data analysis was conducted through data condensation by filtering information from raw data, presenting the data through the integration of information, and drawing conclusions a process that also included data verification. The research results indicate that: Strategies for the recovery of the higher education system must be tailored to the specific challenges faced. The findings identify three types of strategic recovery challenges, consistent with Suwarsono’s theory on corporate recovery. The issues addressed in this study include: student enrollment capacity, manipulation of academic data, and the implementation of academic process standards, which were resolved by UNP Kediri through three actions, namely: 1.) Recovery by forming a crisis management team, carried out by: building good relationships with journalists and forming an internal campus recovery team; 2.) Recovery through the replacement of top leadership, resulting in: commitment to work among organizational stakeholders, an effective communication system, and an improvement in organizational culture toward a more positive direction; 3.) Recovery through a shift in the organization’s strategic orientation, carried out using SWOT analysis, with follow-up actions including: improvements to the LPMPSDM, which encompassed enhancements to service systems and various policies aimed at quality and institutional reform.